Communication, territory, and apparatus: the operationalization of foucaultian genealogy in Communication research - Ferreira, Sérgio Rodrigo da Silva (Passagens: Revista do Programa de Pós-Graduação em Comunicação da Universidade Federal do Ceará, 2024)
The article proposes the application of Michel Foucault's genealogical method to the field of communication and territorialities, especially in research on digital media. Its aim is to map the mutual constitution of a rationality in guiding subjects in the micropolitical dimension (governmentality), of discourses considered true (veridiction), and of processes of subjectivation, as well as the technological intersections on digitized bodies and practices. The study seeks to complexly articulate the fields of subjectivities, algorithmization of life, and power relations, analyzing digital documents that produce truth effects and discourses in devices. It argues that by focusing on these aspects, the issue becomes communicational, involving the analysis of devices, discourses, digital technological arrangements, and the impacts of media on the lives and sociabilities of subjects. Foucauldian genealogy highlights the discursive constraints and freedoms of any historical period, illuminating the historicity of the categories used by individuals to make sense of their lives. It captures how subjects and subjectivities are recognized in the categories of the moment, revealing their "lines of descent" and "emergences." The interest in true discourse in digital environments, with their specific characteristics (invisible audience, collapsed contexts, and fluidity between public and private) guides Foucauldian genealogy as a methodology to access the conditions in which digital technology shapes political relations.